Simulation of Vertically Pollutant Distribution and Deposition in Atmosphere: A Finite Element Approach - Gurung, Prem; Pandey, Hem Raj (Journal of UTEC Engineering Management, 2025)
Nowadays, even in densely populated and industrialized regions, air pollution is a common problem. Air pollution in urban areas has reached crisis proportions, necessitating continuous information on pollution levels. In the present work, we study a one-dimensional unsteady-state model for the distribution of atmospheric pollutants in a vertical direction in the troposphere emitted from a point source; the point source is assumed to be on the lower boundary of the troposphere. We assume that the chemical reaction and diffusivity of pollutants vary with vertical height. So, for simulation purposes, the troposphere is divided into six layers. Hence, the finite element method and the Crank-Nicolson method are used to simulate the model results. The model also includes a study of the effects of dry deposition and gravitational settling velocity in the first layer of the troposphere, measured to the earth’s surface. The results of this study provide insights into the vertical behavior of pollutants and the influence of atmospheric processes near the ground level. This model can be further used to inform policy decisions and optimize pollution mitigation strategies in urban environments.